Pembelajaran Agama Islam Berbasis Moderasi Beragama: Analisis Kebijakan, Implementasi dan Hambatan - Laila Wardati; Darwis Margolang; Syahrul Sitorus (Fitrah: Journal of Islamic Education, 2023)
This study aims to analyze religious moderation-based learning at Bina Taruna 1 Private Vocational School Medan. The focus of the study is on two things, namely the form of implementation and constraints in the implementation of religious moderation-based learning. The research method used is qualitative based on descriptive studies. Data collection techniques used are observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberan techniques, namely data reduction, data display, and drawing conclusions. The results of the study explain that the form of implementation is an in-depth understanding of various religions, respect for diversity, an inclusive curriculum, interfaith dialogue, tolerance practices, collaboration with parents/guardians, training for teachers. The obstacles in implementing religious moderation-based learning are technological developments that are not used properly, intolerant behavior that seems normalized where people who commit religious harassment, for example, often do not receive punishment for their actions, the school also cannot fully supervise students. Because these students also have lives outside the school environment that teachers cannot reach.